Description Of Religuisity And Fear Of Death In Middle Adults - Ahmad Razak (International Journal of Education, Vocational and Social Science, 2023)
Humans in living their lives will experience a span of life, one of which is middle adulthood. Middle adulthood is a transitional period between early adulthood to late adulthood, which is in the age range of 40 to 60 years. Middle adulthood is marked by physical changes due to biological changes such as decreased fertility and health. This condition causes middle-aged adults to worry about death. The fear of death at this age is even higher compared to other age groups. An effective strategy for dealing with the fear of death is to increase religion. The aim of this study is to clarify the relationship between religion and fear of death in middle adulthood. The data collection method is the qualitative research method. Collecting data by means of interviews with research subjects. Based on the results of the study, it was found that the research subjects felt unprepared to face death by feeling anxious, helpless, and wanting to be in the position of other people who had better religious behavior. Subjects viewed that closeness to God Almighty made subjects better prepared to face death. This research has implications that middle adults need to improve their religiosity attitudes and behavior to minimize their fear of death.